Weiterentwicklung des Versuchsaufbaus zur Untersuchung von Polymerschmelzen und -lösungen am Hochdruck-Kapillarrheometer - Hütte, Marvin; Neukötter, Moritz

Highly edge‐connected regular graphs without large factorizable subgraphs - Mattiolo, Davide; Steffen, Eckhard (Journal of Graph Theory)
Keywords: factorization; perfect matchings; regular graphs; r-graphs

Fractional Matchings, Component-Factors and Edge-Chromatic Critical Graphs - Klopp, Antje; Steffen, Eckhard (Graphs and Combinatorics)

Concepts of signed graph coloring - Steffen, Eckhard; Vogel, Alexander (European J. Combinatorics)

Gesellschaftliche Wirkprozesse des Civic Engagement qualitativ erforschen - Dopheide, F.; Freitag, Christine; Koch, L.; Struchholz, C. (Impulse zu Methoden in der deutschsprachigen Civic Engagement-Forschung)

Denk-Wege zu einer religionssensiblen Schulkultur: erziehungswissenschaftliche Perspektiven - Freitag, Christine (Katechetische Blätter)

Gesellschaftlich Wirkprozesse des Civic Engagement qualitativ erforschen - Freitag, Christine (Impulse zu Methoden in der deutschsprachigen Civic Engagement-Forschung)

Untersuchung von Erklärvideos im Physikunterricht - Wirksamkeit von Kohärenz - Hörnlein, Madeleine
Erklärvideos gewinnen auch im Kontext des Physikunterrichts verstärkt an Relevanz. Um zu evaluieren, welche Gestaltungsaspekte ein wirkungsvolles Erklärvideo ausmachen, ist es das Ziel der vorliegenden Masterarbeit herauszufinden, welchen Einfluss die kohärente Gestaltung eines Erklärvideos hat. Dazu wird die Forschungsfrage gestellt: „Welchen Einfluss hat die kohärente Gestaltung eines Erklärvideos auf den dadurch hervorgerufenen Lernzuwachs im Vergleich zu einem in der Hinsicht nicht optimierten Video?“ Um die Forschungsfrage zu beantworten, ist eine quantitative Studie im Prä- und Posttestdesign mit Schüler:innen der Jahrgangsstufe Q1 durchgeführt worden. Außerdem wurde in verschiedenen Kategorien nach einer Bewertung der Videos gefragt. Die Auswertung zeigt, dass durch das optimierte Video mit einem kleinen Effekt bessere Ergebnisse erzielt wurden, diese aber nicht signifikant und auch nicht für alle Aufgaben besser sind. Die Schüler:innen bewerteten das nicht optimierte Video in allen Kategorien besser als das optimierte Video. Auch dieses Ergebnis ist nicht signifikant.

A Comparative Analysis of Consumption: Evidence from a Cultural Goods Market - Kaimann, Daniel; Cox, Joe (Sustainability)
This study uniquely employs a fuzzy-set qualitative comparative analysis (fsQCA) technique to account for complex relationships in consumption. The fsQCA technique assumes that relationships are based on a set–subset relationship. This assumption is fundamental when decision-makers are affected by information asymmetry and are, thus, required to jointly evaluate the credibility and reliability of a range of external signals. This issue also affects consumers in markets for cultural goods, where the quality of products is not known with certainty in advance of the purchase decision. Our study uses fsQCA to establish the effect of different quality signals on consumption in the US market for video game software. Our results show that reviews from professional critics alongside brand extension and multi-platform release strategies act as signals of product quality and, therefore, lead to high sales performance.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

“I will survive”: Online streaming and the chart survival of music tracks - Kaimann, Daniel; Tanneberg, Ilka; Cox, Joe (Managerial and Decision Economics)

The Legacy of Gurus: The Impact of Armin Diel and Joel Payne on Winery Ratings in Germany - Frick, Bernd (Journal of Wine Economics)
Abstract Changes in winery ratings in leading wine guides, that is, improvements as well as deteriorations, are typically attributed to corresponding changes in the quality of the wines produced by the respective winery. What remains unexplored in this context is changes in editorship and/or changes in the composition of the wine tasting teams working for the respective guide. Using data from two particularly prestigious German wine guides (Gault Millau and Vinum), this paper shows that these latter changes have a rather small, yet statistically significant impact on changes in winery ratings. Thus, consumers are well-advised to consider these changes before making their purchasing decision. (JEL Classifications: L21, M30, Q13)
Keywords: Horticulture; General Business; Management and Accounting; Food Science

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 1: [EMIm][OAc] / Water Mixtures - Roos, E.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Optimized Atomic Partial Charges and Radii Defined by Radical Voronoi Tessellation of Bulk Phase Simulations - Brehm, Martin; Thomas, M. (Molecules)

Unraveling Local Structure of Molten Salts via X-Ray Scattering, Raman Spectroscopy, and ab initio Molecular Dynamics - Roy, S.; Brehm, Martin; Sharma, S.; Wu, F.; Maltsev, D.; Halstenberg, P.; Gallington, L.; Mahurin, S.; Dai, S.; Ivanov, A.; Margulis, C.; Bryantsev, V. (J. Phys. Chem. B)

Liquid Structure and Dynamics in the Choline Acetate:Urea 1:2 Deep Eutectic Solvent - Triolo, A.; Pietro, M. E. Di; Mele, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Martinelli, A.; Chater, P.; Russina, O. (J. Chem. Phys.)

Switching Between Proton Vacancy and Excess Proton Transfer Pathways in the Reaction Between 7-Hydroxyquinoline and Formate - Codescu, M.-A.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. A)

Efficient EOM-CC-Based Protocol for the Calculation of Electron Affinity of Solvated Nucleobases: Uracil as a Case Study - Mukherjee, M.; Tripathi, D.; Brehm, Martin; Riplinger, C.; Dutta, A. K. (J. Chem. Theory Comput.)

Liquid Structure of a Choline Chloride-Water Natural Deep Eutectic Solvent: A Molecular Dynamics Characterization - Triolo, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Russina, O. (J. Mol. Liq.)

Qualität sozialer Interaktionen von Jugendlichen mit emotionalen Problemen oder Problemen im Umgang mit Peers im Unterricht – Eine Pilotstudie mit der Experience Sampling Method - Knickenberg, Margarita; Zurbriggen, C.

Gender, special education needs, and inclusion: Evidence from the Perceptopions of Inclusion Questionnaire in Sweden - DeVries, J. M.; Knickenberg, Margarita; Trygger, M.

Academic self-concept, perceptions of inclusion, special needs and gender: Evidence from inclusive classes in Sweden - DeVries, Jeffrey M.; Knickenberg, Margarita; Trygger, Maria (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

Reintroduction of Running After Anterior Cruciate Ligament Reconstruction With a Hamstrings Graft: Can We Predict Short-Term Success? - Pairot de Fontenay, Benoit; Van Cant, Joachim; Gokeler, Alli; Roy, Jean-Sébastien (Journal of Athletic Training)
Context Return to running (RTR) after anterior cruciate ligament reconstruction (ACLR) is a crucial milestone. However, how and when to start a running program are uncertain. Objective To explore the feasibility of a structured program to reintroduce running after ACLR and evaluate the predictive value of potential predictors of short-term success. Design Longitudinal cohort study. Setting Local research center and participants' homes. Patients or Other Participants Thirty-five participants were recruited after ACLR. Intervention(s) Program with a progression algorithm to reintroduce running (10 running sessions in 14 days). Main Outcome Measure(s) The criterion for short-term success was no exacerbation of symptoms. Potential predictors were (1) the International Knee Documentation Committee (IKDC) subjective knee form score, (2) ACL Return to Sport after Injury questionnaire score, (3) quadriceps and hamstrings strength, (4) step-down endurance test, and (5) modified Star Excursion Balance test. Descriptive statistics were performed to study the feasibility of the RTR program, and Poisson regression analysis was used to evaluate predictors of success. Results Of the 34 participants, 33 completed the RTR program. Sixteen participants experienced some temporary exacerbation of symptoms, but only 1 had to stop the program. The initial IKDC score was the only significant predictor of a successful RTR, with an area under the receiver operating characteristic curve of 80.4%. An IKDC cut-off of 63.7/100 differentiated responders and nonresponders with the highest sensitivity and specificity (77.8% and 75.0%, respectively). A participant with an IKDC score above this threshold had a 3-fold greater chance of success. Conclusions Our results confirm the feasibility of our RTR program and progression algorithm after ACLR. Clinicians should use an IKDC score of >64 as a criterion to reintroduce running after ACLR to increase the likelihood of short-term success.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

An Exploratory Meta-Analytic Review on the Empirical Evidence of Differential Learning as an Enhanced Motor Learning Method - Tassignon, Bruno; Verschueren, Jo; Baeyens, Jean-Pierre; Benjaminse, Anne; Gokeler, Alli; Serrien, Ben; Clijsen, Ron (Frontiers in Psychology)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory, and to date, no overview exists that compares the effects of DL to other motor learning methods. Objective: To evaluate the effectiveness of DL in comparison to other motor learning methods in the acquisition and retention phase. Design: Systematic review and exploratory meta-analysis. Methods: PubMed (MEDLINE), Web of Science, and Google Scholar were searched until February 3, 2020. To be included, (1) studies had to be experiments where the DL group was compared to a control group engaged in a different motor learning method (lack of practice was not eligible), (2) studies had to describe the effects on one or more measures of performance in a skill or movement task, and (3) the study report had to be published as a full paper in a journal or as a book chapter. Results: Twenty-seven studies encompassing 31 experiments were included. Overall heterogeneity for the acquisition phase (post-pre; I 2 = 77%) as well as for the retention phase (retention-pre; I 2 = 79%) was large, and risk of bias was high. The meta-analysis showed an overall small effect size of 0.26 [0.10, 0.42] in the acquisition phase for participants in the DL group compared to other motor learning methods. In the retention phase, an overall medium effect size of 0.61 [0.30, 0.91] was observed for participants in the DL group compared to other motor learning methods. Discussion/Conclusion: Given the large amount of heterogeneity, limited number of studies, low sample sizes, low statistical power, possible publication bias, and high risk of bias in general, inferences about the effectiveness of DL would be premature. Even though DL shows potential to result in greater average improvements between pre- and post/retention test compared to non-variability-based motor learning methods, more high-quality research is needed before issuing such a statement. For robust comparisons on the relative effectiveness of DL to different variability-based motor learning methods, scarce and inconclusive evidence was found.
Keywords: General Psychology

Effective Attentional Focus Strategies after Anterior Cruciate Ligament Reconstruction: A Commentary - Singh, Harjiv; Gokeler, Alli; Benjaminse, Anne (International Journal of Sports Physical Therapy)
Individuals after anterior cruciate ligament reconstruction (ACLR) have a high rate of reinjury upon return to competitive sports. Deficits in motor control may influence reinjury risk and can be addressed during rehabilitation with motor learning strategies. When instructing patients in performing motor tasks after ACLR, an external focus of attention directed to the intended movement effect has been shown to be more effective in reducing reinjury risk than an internal focus of attention on body movements. While this concept is mostly agreed upon, recent literature has made it clear that the interpretation and implementation of an external focus of attention within ACLR rehabilitation needs to be better described. The purpose of this commentary is to provide a clinical framework for the application of attentional focus strategies and guide clinicians towards effectively utilizing an external focus of attention in rehabilitation after ACLR. Level of Evidence 5
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation

Rehabilitation strategies of Flemish physical therapists before and after anterior cruciate ligament reconstruction: An online survey - Dingenen, Bart; Billiet, Bart; De Baets, Liesbet; Bellemans, Johan; Truijen, Jan; Gokeler, Alli (Physical Therapy in Sport)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Model-based Continuous Experimentation for Software Product Prototypes - N., N.

Lightweight Process Engine for Situation-specific Development of Business Models for Digital Platforms - N., N.

Development and Evaluation of a Multi Platform Approach for Augmented Reality Product Configuration - N., N.

Model-based Feature Backlog Synchronization for Dual-Track Development Methods - N., N.

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.

Device-Independent Security Proofs Via Entropy Accumulation - Anonymous, Anonymous

David und Salomo im Koran: ein Komparativ-theologischer Ansatz - Saad, Nadia (Methoden der Darstellung und Analyse interreligiöser Diskurse)

Reading Iqbal in the Light of Kierkegaard; towards an Existentialist Approach to Islam - Mir Sadri, Seyedeh Saeideh; Nasiri, Mansour (Philosophy East and West)

Fratelli e sorelle tutti. Die Sozialenzyklika aus islamischer Sicht - Mir Sadri, Seyedeh Saeideh (Amos-international)

"Ein altes Familientalent" - Kinderzeichnungen aus der Familie der Brüder Grimm (1. Hälfte 19. Jh.) in der Grimm-Sammlung der Stadt Kassel. Germany - Eikermann, Larissa (Das Erbe der Kinder: Provenienzforschung und Sammlungsgeschichte von Kinder- und Jugendzeichnungen: Museen, Archive, private Kollektionen und "verschwundene Sammlungen" = The children's heritage: provenance research and the history of children's and youth drawings collections: museums, archives, private holdings and "lost collections")

Children´s drawings on Pippi & Co. - A visit to the Astrid Lindgren Archive in the Royal Library of Stockholm. Sweden - Eikermann, Larissa (Das Erbe der Kinder: Provenienzforschung und Sammlungsgeschichte von Kinder- und Jugendzeichnungen: Museen, Archive, private Kollektionen und "verschwundene Sammlungen" = The children's heritage: provenance research and the history of children's and youth drawings collections: museums, archives, private holdings and "lost collections")

Begegnungslernen in den Kerncurricula des islamischen Religionsunterrichts - Kamcili-Yildiz, Naciye (Interreligiöse Öffnung durch Begegnung. Grundlagen - Erfahrungen - Perspektiven im Kontext des christlich-islamischen Dialogs)